KEJADIAN STROKE ISKEMIK PADA PASIEN POSITIF COVID19 TERKONFIRMASI DI RUMAH SAKIT UNIVERSITAS INDONESIA - Rakhmad Hidayat,*,** , Gemia Clarisa Fathi,*** Ramdinal Aviesena Zairinal,**, Raden Rara Diah Handay (Neurona Majalah Kedokteran Neuro Sains, 2021)
CORONAVIRUS DISEASE 2019 COVID19 IS NOT ONLY DISRUPTS THE RESPIRATORY SYSTEM IT CAN DISRUPT VARIOUS ORGAN SYSTEMS ONE OF WHICH IS THE CENTRAL NERVOUS SYSTEM INDONESIA STILL HAS A LITTLE LITERATURE THAT DISCUSSES COVID19 AND ITS RELATION TO ISCHEMIC STROKE THIS STUDY AIMS TO REPORT THE COURSE OF ISCHEMIC STROKE CASES IN PATIENTS WHO HAVE BEEN CONFIRMED POSITIVE FOR COVID19